Perceptions of healthcare providers on benefits, risks and barriers regarding intradialytic exercise among haemodialysis patients - Zelko, Aurel; Skoumalova, Ivana; Kravcova, Denisa; Dankulincova Veselska, Zuzana; Rosenberger, Jaroslav; Madarasova Geckova, Andrea; van Dijk, Jitse P; Reijneveld, Sijmen A (International journal of qualitative studies on health and well-being, 2024)
PURPOSE: Clinical guidelines call for the inclusion of exercise interventions in every patient's dialysis session, but these recommendations are rarely adopted. Healthcare providers play a key role in this. Therefore, the aim of this study was to explore how healthcare providers perceive the benefits, risks and barriers of intradialytic exercise (IDE). METHODS: We conducted 21 individual, semi-structured interviews with 11 nurses, 5 nephrologists, 3 training assistants and 2 managers from two dialysis centres in Slovakia. Verbatim transcripts of digitally recorded interviews were thematically analysed using MAXQDA®. RESULTS: Participants reported the benefits of IDE as improvements in patients' physical and psychosocial functioning, independence and self-efficacy, clinical profile and quality of therapy. As risks of IDE, they most frequently reported exercise-related damage to vascular access, insufficient individualization of training and musculoskeletal injuries. The presence of psychological problems among patients was reported as a major barrier for initiating and maintaining patients' exercise. Other reported barriers included limitations in financial and personnel resources of haemodialysis care. CONCLUSIONS: Safe and sustainable implementation of IDE, which might improve a patient's well-being, need to be prescribed in alignment with the patient's clinical profile, be delivered individually according to the patient's characteristics and requires adjustments in the available resources.
Keywords: Attitude of Health Personnel; Self Efficacy; Health Personnel; lidé; Renal Dialysis; cvičení; Exercise; dialýza ledvin; postoj zdravotnického personálu; sebeuplatnění; zdravotnický personál; Humans